The The Flouting Maxim Analysis of Rudy Ayoub’s Joke About His Arabian Dad - Gabriella Novainty Soedjarwo (Journal of Pragmatics Research, 2026)
Language is not only a tool for communication but also a mirror of cultural values, as seen in forms such as proverbs, poems, short stories, and especially jokes. Humour, in particular, often relies on shared cultural understanding, making cultural context essential for interpretation. In the field of pragmatics, jokes can be analysed through Gricean conversational maxims, where intentionally flouting these maxims creates a comedic effect. This study investigates how Rudy Ayoub uses humour in his sketches depicting father-son relationships within Arabian parenting culture. By transcribing and coding selected video excerpts, this research applies pragmatic analysis to examine the strategies behind Rudy’s jokes and the role of cultural norms in shaping them. The findings reveal that Rudy most frequently flouts the maxim to produce humour by exaggerating the inconsistencies and unpredictability of his father’s expressions of affection—sometimes warm, sometimes distant. These jokes not only entertain but also reflect underlying values in Arabian parenting, highlighting the emotional complexity and social expectations within the family. This study underscores that humour is not merely a linguistic play but a culturally grounded phenomenon, where pragmatic strategies and societal norms intersect to create laughter and insight. By analysing Rudy’s sketches, the research offers a vivid example of how culture and conversational pragmatics work together in modern comedic expression.